(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Tephrology is a broad term that comprises all the aspects related to “tephra” studies (stratigraphy, chronology, petrology, sedimentology, chemistry, Froggat and Lowe, 1990; Lowe and Hunt, 2001) (Fig. 1). In Argentina, tephrological studies have significantly increased recently as a result of the increment in the Southern Andes volcanic activity affecting the country in the last two decades (E.g.: Corbella et al., 1991a,b; Stern, 1991; Mazzoni and Destéfano, 1992; Nillni et al., 1992; Gonzalez Ferrán, 1993; Naranjo et al., 1993; Scasso et al., 1994; Nillni and Bischene, 1995; Haberle and Lumley, 1998; Villarosa et al., 2002; Kilian et al., 2003; Naranjo and Stern, 2004; Orihashi et al., 2004; Stern, 2004; Scasso and Carey, 2005; Daga et al., 2008; Watt et al., 2009; Martin et al., 2009; Leonard et al., 2009; Rovere et al., 2009, 2011; Wilson et al., 2009, 2012). The eruption of Quizapú volcano (Volcanic Complex Azul-Descabezado Grande, Province of Talca, Chile, 36,67°S-70,77°W, maximum height of 3788 m a.s.l.), that occurred on April 10, 1932, represented one of the largest eruptions worldwide in the 20th Century. It affected extensive regions of Argentina as well as many coastal areas of the Southwestern Atlantic Ocean as a result of the prevailing westerly winds, and specifically impacted dramatically in regions located nearby the source volcano (Department of Malargüe, Province of Mendoza, west-central Argentina, Fig. 2). The wide spreading of the resulting tephras and its easy reconnaissance in the field provides a great opportunity for detailed studies about the eruption and its products. Results on the eruptive aspects and tephras dispersion and deposition from this eruption were published by some authors (Lunkenheimer, 1932; Kittl, 1933; Walker, 1981, Hildreth and Drake, 1992, González Ferrán, 1993; Ruprecht and Bachmann, 2010; Ruprecht et al., 2012). In this contribution the sedimentological, mineralogical and chemical characteristics of the tephra deposits occurring at the Llancanelo Lake and surroundings, located 140 km east (downwind) of the Quizapú volcano, are studied based on grain-size, petrographic and electron microscope analysis (SEM) as well as semiquantitative chemical determinations by Energy Dispersive Spectrometer (EDS). The obtained results, when compared with the results of analyses performed by other authors in tephras from the 1932 eruption of the Quizapú volcano, allow attributing the studied tephra layer to this eruption. On these bases, diverse aspects related to the depositional and post-depositional aspects of the tephras are herein discussed, as well as some environmental changes produced by the eruption. On the other hand, this paper contributes to a systematic and comparative classification of volcanic hazard in health and society that serves as base-studies for better understanding other more recent Southern Andes eruptive events that affected Argentina (Hudson, Copahue, Chaitén, Llaima, Peteroa and Puyehue-Cordón Caulle volcanoes). The eruption of Quizapú volcano in 1932 was one of the most important events among a long history of activity of this volcanic complex (Smithsonian Institution, 2012). It had a plinian character and threw into the atmosphere enormous amounts of tephras varying between 5 and 30 km3 according to different authors (Kittl, 1933; González Ferrán, 1993; Hildreth and Drake, 1992; Ruprecht and Bachmann, 2010), producing a dramatic impact in society, agriculture and local economies in the downwind neighboring affected regions (Abraham and Prieto, 1993; González Ferrán, 1993). The tephra deposits were very uniform in thickness with a notable decreasing grain-size tendency with distance from the source volcano, ranging from 6 cm in neighboring areas and reaching silt and clay sizes around 100 km east (Kittl, 1933; Hildreth and Drake, 1992). The horizon of tephras was recognized as a regional level in a number of natural outcrops pits and excavations, as well as in sediment cores recovered from short drillings (Fig. 3). The tephra level was affected by compaction and post-depositional transformations after 80 years of burying and exposure to weathering and pedogenetic processes, although most of the original characteristics are very well preserved. The sedimentary sequence in which the tephra level is included was recognized regionally by surface and subsurface surveys based on geoelectrical methods and short drillings (Violante et al., 2010; Osella et al., 2010, 2011; de la Vega et al., 2012). The sequence is composed of light brown sandy-silty sediments of lacustrine and eolian origin with high volcaniclastic content and interbedding of buried soils and evaporites (Rovere et al., 2010a,b; D´Ambrosio et al., 2011). In some profiles (P19 and P42, Fig. 3) located in marginal areas east of the lake, the tephra layer overlies lacustrine deposits and is in turn covered by eolian deposits; this indicates that the lake borders were filled with tephra during the eruption and definitively desiccated, and were later covered by eolian deposits probably as a result of the aridity of the climate that followed the eruption. On the other hand, in the lacustrine plain west of the lake the tephra layer was not found; a possible explanation for this is either post-depositional erosive processes or not deposition, as some places could have been, at the moment of the eruption, part of the lacustrine body with higher water energy, and therefore the ash was dispersed without leaving any recognizable deposit. Northwest of the lake, the tephra deposit was found overlying a buried soil containing burned vegetation remains (profile P45, Fig. 3), suggesting high temperatures of the ash fall with consequent burning of vegetation, as it was also documented in other regions of the world (Carson et al., 1990; Seymour et al., 1993). In the lacustrine coastal plain of the lake, tephra layers were found overlying eolian deposits (profiles P5, P21 and P26, Fig. 3). Tephra´s grain-size indicates varied sizes between very fine and medium sand. Sediments are poorly sorted and statistical grain-size distributions (Table 1, Fig. 4) are bimodal with two well-marked populations separated at the size-range of 3-3,5 ? (88- 125 µm). Population 1 is coarser with mode between 1 and 2 ? (250 to 500 µm), whereas Population 2 is finer with mode between 4 and 7 ? (63 to 8 µm). This bimodal distribution is typical for distal tephras (Bonadonna and Houghton, 2005; Rose and Durant, 2009). The lower-sized population contains the “respirable particles” (PM10 <10 µm, Horwell et al., 2003, Horwell and Baxter, 2006). Optical microscopy allowed obtaining the bulk mineralogical composition and details of the ash shards. Bulk composition is: 59% volcanic glass, 40% crystals (in decreasing order: plagioclases, magnetite, hornblende, pyroxenes, quartz, olivine and ilmenite) and 1% lithoclasts (possibly andesitic volcanic pastes). Glass is mainly composed of fibrous, pumiceous shards with vesicular microcavities, most of them tubular and elongated with minor amount of cuspate, blocky and platy individuals (Figs. 5, 6 and 7). Besides, the minerals contain vesiculated glass adhered to the crystals. SEM analyzes were aimed at observing details of the particle´s shapes and surface characteristics. They are all of varied shapes ranging from equidimensional, elongated (prismatic) and irregular, from rounded to angular with sharp edges, with striations and different degrees of vesicularity (Figs. 6 and 7). Glass shards show a major composition of light brown glass (possibly sideromelano) although dark glass is also present, and they show some coating. Its vitreous textures were defined following the clasification by Miwa et al. (2009), as massive with two types of surfaces, smooth-uniform (S-type) and not-smooth-irregular (NS-type) with alveoli and hollows (Fig. 7). The coating consists of highly cohesive small particles (<25 µm, and hence they correspond to the “respirable” sizes) which can be partially adhered by some melting process to the larger particles. EDS revealed predominance (in decreasing order) of SiO2 (up to 70%), Al2O3 (up to 15%), with lesser amounts of K, Na, Ca, Zn, Mg, Cu, Fe y Ti (Fig. 7, Table 2). The three last mentioned components are abundant as oxides included in the ash. K is an important component in accordance to the high K content of the Volcanic Complex Cerro Azul - Descabezado Grande - Quizapú (Backlund, 1923), which seems to have been proportionally increased in percentage by desilication of the tephra during transport (Aomine and Wada, 1962). On the other hand, high concentrations of Cu were found in some samples (Fig. 8, samples P5 III and P20 I in Table 2), what is preliminary associated to post- depositional alteration of tephras by weathering and transformation in alofana and halloysite with incorporation of high Cu content. The sedimentological and semi quantitative chemical characteristics of the studied tephras from Quizapú eruption, together with the erupted volume of tephras and the volcanic column height mentioned in the available bibliography, are compatible with an explosive plinian eruption (Walker, 1981; Newhall and Self, 1982; Simkin and Siebert, 1994; Bonadonna and Houghton, 2005; Rose and Durant, 2009; Carey et al., 2009; Gislason et al., 2011; Smithsonian Institution, 2012). This eruption seriously affected the southern Mendoza province where Llancanelo lake is settled, producing a reduction of the lake size, the burying and burning of soils and the increasing in aridity of the region. These effects can be easily observed in the field according to the stratigraphic relations of the Quizapú Volcano tephras level with the under- and overlying lacustrine, eolian and buried soils levels. The eruption caused the collapse of the local farming, agriculture and livestock economies as well as heavily impacted in society. The obtained sedimentological, mineralogical, petrographical and chemical characteristics of the tephras reveal fractioning processes during the eruptive and post-eruptive phases with deep post- eruptive changes in the particles concentrates, following the concepts by Rose and Durant (2009). Additional complications to the resulting tephras deposits arise from aggregation processes, as it was documented in Chaitén Volcano tephras erupted in 2008 (Watt et al., 2009). Agglutination of particles also occurred, possibly as a result of primary salts formed by exsolution during the aerial transport and deposited as coatings on the particles surfaces, that later reacted in contact to atmospheric fluids (Delmelle et al., 1980, 2007, Gislason et al., 2011); however, preservation of such coatings is unlikely due to post-depositional processes such as dissolution, weathering, alteration by phreatic activity, secondary recrystallization, etc. Particles surface features reveal two types of textures following the concepts by Miwa et al. (2009), which reveal eruptive characteristics, energy of the transport process, gases content and post-depositional processes. SEM analysis show typical characteristics of an andesitic magmatic eruption or partially fluid with hydromagmatic components. Particles morphology and the thickness of vesicle´s walls would preliminary indicate relative fluidity and medium viscosity, as well as the cooling velocity in the volcanic conduit. Smaller particles (finest fractions of Population 2) adhered and partially cemented to the larger particles would indicate pulverization during fragmentation (Wohletz and Krinsley, 1982). Particles containing high Cu proportions are thought to have been produced by transformation of volcanic glass in alofana and hydrated halloysite during weathering, what results in desilication and increasing Cu content (Fig. 8), although further studies are needed on this matter. On the other hand, the SiO2-K2O relation (Fig. 9) arranges the samples in a graphic field close to that reported by other authors (Fierstein et al., 1989; Hildreth and Drake, 1992; Ruprecht et al., 2012), although with a slight decreasing in Si content that is associated to differential particles deposition according to the distance from the source volcano and desilication. The reduction in the lake size evidenced by the regional geology and stratigraphic sequences (Violante et al., 2010; de la Vega et al., 2012) as well as the burning of vegetation underlying the Quizapú tephras layer, agree with oral versions from aged inhabitants of the region, who mentioned the fallout of “hot” ash and the drying of large lacustrine areas during the months that followed the eruption (Ovando and Ramires, 2009). Both the reduction in the lake size as well as the capping of the tephra layer by eolian deposits also demonstrate the aridity of the region that followed the eruption, as stated by Abraham and Prieto (1993). The volumes of ejected fine tephras of sizes smaller than 10 µm, and particularly those smaller than 4 µm, which are considered to affect human health as they can produce respiratory diseases -particularly if they have high silica content and sharp-shaped (Horwell et al., 2003)-, reveal the potential harmful of these materials. Grain-size distributions of Quizapú tephras show around 6% of particles <10 µm. If it is considered the 150 ton km-2 of tephra released by the eruption (according to the estimations by González Ferrán, 1993), hence about 9 ton km-2 of respirable particles could have been incorporated into the atmosphere, from which 35% (3.15 ton km-2) is even lesser than 4 µm in size. These numbers must be taken into account in order to evaluate health impact. Studies of this kind contribute to develop methodologies in tephrological analysis to be applied to other recent eruptive events and for evaluating in a multidisciplinary way the volcanic hazard on environment and society.